PO53 Chrysin and Genistein, from natural products to behavioral pharmacology - BERNAL, BLANDINA; Guillén-Ruiz, Gabriel; Rodríguez Landa, Juan Francisco (Revista Productos Naturales, 2025)
Vascular plants naturally produce biologically active secondary metabolites that influence mammalian cellular function. Among these, polyphenols—particularly flavonoids—are widely distributed throughout the plant kingdom and are responsible for many of the colors, flavors, and medicinal properties found in fruits, flowers, herbs, and beverages such as tea and wine [1]. This study focuses on two flavonoids, chrysin and genistein, which have demonstrated pharmacological effects relevant to the treatment of anxiety and depression [2;3].